Dress Rehearsal for Shelley: Scovel Richardson and the Challenge to Racial Restrictions in St. Louis - Colin Gordon (Washington University Journal of Law and Policy, 2022)
Throughout the twenty-first century, St. Louis was one of the most segregated metropolitan cities in the nation. This problematic setting allowed the city to become ground zero for the legal battle against racial segregation. While many are aware of the historic ruling in Shelley v. Kraemer, which prohibited state enforcement of racially restrictive deed covenants, less is known about the distinct local history in St. Louis that set the stage for this case. This Essay discusses the history of racially restrictive covenants in the city and the subsequent legal challenges that occurred on the state and local level. Gordon focuses on a key figure in this history, Scovel Richardson, and his seminal case Dolan v. Richardson. The Essay argues that Richardson’s case served as a precursor to Shelley and explains the substance and history of legal arguments deployed by Richardson in the case. Gordon explains that, despite its unsatisfying outcome, this challenge to restrictive covenants in Richardson opened the door for the groundbreaking ruling in Shelley.
Keywords: Shelley v. Kraemer; Segregation; St. Louis; Scoval Richardson; Dolan v. Richardson; Restrictive Covenants